Cardiometabolic risk factors among children and adolescents with overweight and Class 1 obesity: A cross-sectional study. Insights from stratification of Class 1 obesity - Nakhleh, Afif; Sakhnini, Rizan; Furman, Eyal; Shehadeh, Naim (Frontiers in Endocrinology, 2023)
Context: Severe childhood obesity is associated with increased prevalence of cardiometabolic risk factors (CMRFs). Among children with Class 1 obesity, higher BMI may indicate greater cardiometabolic risk. Class 1 obesity reflects a wide spectrum of BMI values. Each 10% increase in BMI above the 95th percentile is equivalent to an average increase of 2.15 kg/m2 and 2.75 kg/m2 in BMI among children and adolescents, respectively. Such increments may be of clinical importance. Objectives: The study aimed to determine the prevalence and clustering of CMRFs in children and adolescents with BMI 110%-119% of the 95th BMI percentile. Methods: A cross-sectional analysis of data, from an Israeli health maintenance organization, of children and adolescents (5-17 years) with overweight or Class 1 obesity, and at least one measurement of lipid profile during Jan/2020-May/2021. CMRFs were defined as abnormal lipid profile, elevated alanine aminotransferase, hypertension, and prediabetes or diabetes. Study groups included overweight and Class 1 Obesity-A (BMI < 110%) and Obesity-B (BMI ≥ 110%) of the 95th BMI percentile. Results: Of 7211 subjects included, 40.2% were overweight, 50.3% obesity-A, and 9.5% obesity-B. Multivariable analyses showed that children and adolescents from the Obesity-B group had increased odds for higher triglycerides, LDL cholesterol, and ALT levels; and lower HDL cholesterol levels, as compared to Obesity-A. The odds of prediabetes (insignificant) tended to be higher in the Obesity-B group, which was associated with increased CMRFs clustering. Conclusions: Among children and adolescents with Class 1 obesity, BMI ≥ 110% of the 95th percentile was associated with higher prevalence and clustering of CMRFs.